Impact of agr Functionality on the Outcome of Patients with Methicillin-Susceptible Staphylococcus aureus Bacteremia - Jeong Eun Lee; Shinwon Lee; Sohee Park; Soon O. Lee; Sun H. Lee (Microbiology Spectrum, 2021)
ABSTRACT Dysfunctional accessory gene regulator (agr) is associated with unfavorable outcomes in invasive methicillin-resistant Staphylococcus aureus infections. However, it is unknown whether this association persists in methicillin-susceptible Staphylococcus aureus bacteremia (MSSA-B). This study evaluated the association between agr dysfunction and mortality in patients with MSSA-B. This retrospective cohort study included MSSA-B patients (≥15 years) enrolled from June 2014 to June 2019 and retrospectively collected their demographic and clinical information. Stored causative strains were measured for agr functionality by δ-hemolysin production assays. Among 244 MSSA-B patients, 91 (37.3%) and 153 (62.7%) had dysfunctional and functional agr MSSA-B, respectively. Ninety-day mortality occurred in 18.7% and 17.6% dysfunctional and functional groups, respectively (P = 0.97). Kaplan-Meier analysis showed that mortality due to dysfunctional agr MSSA-B was not significantly higher (P = 0.82). Age, sites, the severity of infection, and comorbidity adjusted hazard ratio (aHR) of the dysfunctional group for 90-day mortality was 1.303 (95% confidence interval [CI], 0.698 to 2.436, P = 0.41). Mortality due to MSSA-B with sequential organ failure assessment (SOFA) scores of 2 to 5 was significantly higher in the dysfunctional group (P = 0.03), and the dysfunctional agr aHR for 90-day mortality was 3.260 (95% CI, 1.050 to 10.118, P = 0.04). The agr dysfunction of causative organisms can have a significant effect on the outcomes of MSSA-B in patients with moderate severity (SOFA scores 2 to 5). IMPORTANCE Few studies have examined the association between methicillin-susceptible Staphylococcus aureus (MSSA) infection and accessory gene regulator (agr) functionality. We evaluated the association between agr dysfunction and mortality in patients with MSSA bacteremia. Dysfunctional agr is associated with lower survival in MSSA bacteremia patients with moderately severe sequential organ failure assessment (SOFA) scores of 2 to 5. We found that the agr functionality of causative organisms may have an effect on patients’ outcomes in MSSA like in methicillin-resistant S. aureus.